2016
DOI: 10.1016/j.chemosphere.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of legacy and “novel” brominated flame retardants in different particle size fractions of indoor dust in Birmingham, United Kingdom

Abstract: This study investigates the particle size distribution of eight polybrominated diphenyl ethers (PBDEs) and five "novel" brominated flame retardants (NBFRs) in settled house dust. Elevated surface dust (ESD) and floor dust (FD) were collected from 5 homes in Birmingham, UK, yielding a total of 10 samples. Each sample was fractionated into three different particle sizes: 125-250 μm (P1), 63-125 μm (P2) and 25-63 μm (P3). Non-fractionated bulk dust samples (BD) were also analysed. BDE-209 predominated, comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
(54 reference statements)
2
16
1
Order By: Relevance
“…Living rooms from the United Kingdom were shown to exhibit higher levels of NBFRs compared to kitchens, with DBDPE having the highest concentrations in both areas (Kuang et al, 2016). However, in another UK study, BEH-TEBP exhibited the highest concentrations in house dusts (Al-Omran and Harrad, 2016). Similar results were obtained in a German study, where BEH-TEBP was the dominant NBFR in house dusts (Fromme et al, 2014).…”
Section: Dp and Nbfrs In The Indoor Environmentsupporting
confidence: 73%
See 2 more Smart Citations
“…Living rooms from the United Kingdom were shown to exhibit higher levels of NBFRs compared to kitchens, with DBDPE having the highest concentrations in both areas (Kuang et al, 2016). However, in another UK study, BEH-TEBP exhibited the highest concentrations in house dusts (Al-Omran and Harrad, 2016). Similar results were obtained in a German study, where BEH-TEBP was the dominant NBFR in house dusts (Fromme et al, 2014).…”
Section: Dp and Nbfrs In The Indoor Environmentsupporting
confidence: 73%
“…This study also showed similarity in f anti ratios between hair and dust suggesting that dust ingestion might be one of the major pathways for human exposure to DP (Zheng et al, 2010). According to a Pakistani study by Khan et al (2016), DP levels were heavily present indoors but not outdoors, and high correlations were observed Peng et al, 2017Peng et al, 2017Peng et al, 2017Peng et al, 2017Kurt-Karakus et al, 2017Kurt-Karakus et al, 2017Kurt-Karakus et al, 2017Kurt-Karakus et al, 2017Kurt-Karakus et al, 2017Al-Omran et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Khan et al, 2016Fan et al, 2016Fan et al, 2016 Sum of all DPs, including syn-and anti-DP. Cars (n = 9) House (n=81) House (n = 10) Elementary school (n =18) E-waste recycling (n = 9) E-waste recyclin...…”
Section: Dp and Nbfrs In The Indoor Environmentmentioning
confidence: 94%
See 1 more Smart Citation
“…These patterns suggest that while the indoor environment shared by mothers and their children may be an important source of BFR exposure, age-specific behaviors may contribute to differences in exposure pathways within the home. Studies have shown that the distribution of house dust particles size varies by the spatial positioning of the settled dust [ 18 , 19 ] and that concentrations of PentaBDE congeners, but not BDE-209 or TBB, vary by dust particle size, with higher concentrations typically detected in smaller size fractions [ 20 ]. These properties may partially explain our lack of a significant association between ΣPentaBDE measured in house dust and on handwipes, as dust on surfaces and handwipes may be characterized by different dust particle size distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other emerging FRs, the environmental occurrence of EH-TBB and FM550 components is expected to be mainly in indoor dust. Residential dust in the UK contained median concentrations of EH-TBB and BEH-TEBP at 4 -23 (median = 5.8) and 80 -3187 (median = 320) ng/g, respectively (Al-Omran and Harrad, 2016). In the U.S.A., house dust samples from California collected in 2011 showed higher levels of FM550 components than those collected in 2006.…”
Section: Introductionmentioning
confidence: 95%